2016
DOI: 10.1111/acer.12991
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the Vesicular Monoamine Transporter 1 (VMAT1/SLC18A1) Gene and Alcohol Withdrawal Severity

Abstract: This study shows that genetic variants in VMAT1, including the functional SNP rs1390938, contribute to the severity of AW in patients of European descent. Our data show for the first time a role of presynaptic neurotransmitter release in AW severity. This finding could contribute to identifying patients at risk for severe AW and shed light into the pathophysiology of AW and its treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Lohoff concluded that VMAT1 variants play a role in emotional processing as well as risk for psychopathology. These findings buttress association studies showing that the minor A allele of VMAT1 variant rs1390938 has been associated with lower risk of alcohol use dependence (Dutta et al, 2016;Vaht, Kiive, Veidebaum, & Harro, 2016), anxiety-related personality traits (Lohoff et al, 2008), maladaptive impulsivity, anxiety, depressiveness, and neuroticism (Vaht et al, 2016). Closely related VMAT2 (SLC18A2) SNPs have been associated with phenotypes such as depression in elderly men (Christiansen et al, 2007), alcohol dependence (Schwab et al, 2005), and posttraumatic stress disorder (Solovieff et al, 2014).…”
Section: Vesicular Monoamine Transportersmentioning
confidence: 72%
“…Lohoff concluded that VMAT1 variants play a role in emotional processing as well as risk for psychopathology. These findings buttress association studies showing that the minor A allele of VMAT1 variant rs1390938 has been associated with lower risk of alcohol use dependence (Dutta et al, 2016;Vaht, Kiive, Veidebaum, & Harro, 2016), anxiety-related personality traits (Lohoff et al, 2008), maladaptive impulsivity, anxiety, depressiveness, and neuroticism (Vaht et al, 2016). Closely related VMAT2 (SLC18A2) SNPs have been associated with phenotypes such as depression in elderly men (Christiansen et al, 2007), alcohol dependence (Schwab et al, 2005), and posttraumatic stress disorder (Solovieff et al, 2014).…”
Section: Vesicular Monoamine Transportersmentioning
confidence: 72%
“…Genetic changes in VMAT1 could thus affect the amount of monoamines contained in vesicles, which is in turn released from the nerve terminal, affecting downstream signaling. A recent study has shown that VMAT1 knockout in mice lead to differential dopamine signaling [52], and several other studies have revealed the association of the 136Thr with a variety of psychiatric phenotypes including alcohol dependence [38, 53], bipolar disorders [34], autism [39], anxiety [37, 38], maladaptive impulsivity, depressiveness, and neuroticism [38]. A functional neuroimaging study has revealed that this variant has distinct influences on activity of the prefrontal cortex and amygdala [44], both of which play crucial roles in emotional processing, that may underlie the socioemotional differences observed in the abovementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…SLC18A1 maps to chromosome 8p23.1, a region of genes associated with personality traits (21). SLC18A1 rs1390938/Thr136Ile is associated with mood, depression, personality, and alcohol use in the general population (22,23). Individuals homozygous for the 'hyperfunction' allele (AA; Ile/Ile) appear to be more resilient to these disorders (24).…”
Section: Discussionmentioning
confidence: 99%